Imunitas Advokat dan Kemanfaatan Hukum: Studi Kasus Potensi Kriminalisasi Profesi dalam Perkara Hendra Sianipar - Citra Azra Amalia; Rafif Gadi Maulana; Shelomita Azalia Widiyaningrum; Arie Sukanti Siagian; Baidhowi Baidhowi (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The legal profession plays a vital role in the judicial system to ensure the principle of equality before the law as well as fair and accountable legal proceedings. In accordance with Law No. 18 of 2003 on Advocates, an advocate is an autonomous, independent, and accountable legal professional who is granted immunity as stipulated in Articles 14, 15, and 16, which provide protection from civil and criminal claims when acting in good faith while performing their duties. However, in practice, the scope of this immunity often leads to differing interpretations, particularly regarding the parameters of “good faith” and the scope of “professional duties,” which can result in the criminalization of lawyers. This is evident in the case of Hendra Sianipar, where a lawyer’s actions in exercising legal authority were instead subject to criminal prosecution. This study aims to examine the limits of attorney immunity and explore the potential for criminalization of this profession using a normative legal approach combined with a legal utility analysis. The findings of this study indicate that attorney immunity is not absolute but is limited by good faith, compliance with the law, and professional ethics, thus requiring clearer and more balanced clarification of these limits.